Architecture of a heterogeneous marine internet of things for intelligent offshore engineering - Zhenhua FU; Jie LI; Fei JI; Hua YU (Dianxin kexue)
With the development of the offshore engineering towards intelligence and informatization, the safety and environmental monitoring technology is demanding for offshore operating platforms.A heterogeneous marine IoT architecture for the intelligent offshore engineering was proposed.The network was based on underwater acoustic communication technology, marine radio wireless communication, intelligent gateway and cloud platform to realize remote and online monitoring offshore engineering and platforms.The main modules, and some of the key technologies and challenges involvedin the network were introduced.The network architecture can provide a reference for the realization of an intelligent offshore engineering equipment and platforms.